2018
DOI: 10.1089/neu.2017.5114
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Cerebrovascular Function in Chronic Traumatic Brain Injury

Abstract: Traumatic cerebrovascular injury (TCVI) is a common pathologic mechanism of traumatic brain injury (TBI) and presents an attractive target for intervention. The aims of this study were to assess cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) using magnetic resonance imaging (MRI) to assess their value as biomarkers of TCVI in chronic TBI, characterize the spatial distribution of TCVI, and assess the relationships between each biomarker and neuropsychological and clinical assessments. Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 40 publications
3
66
0
Order By: Relevance
“…Furthermore, a significant group difference in dorsal anterior cingulate was found. Amyot et al found significant reductions in mean global, GM, and WM cerebrovascular reactivity in chronic TBI individuals by BOLD analysis . However, no significant group difference for CBF was found by ASL analysis.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, a significant group difference in dorsal anterior cingulate was found. Amyot et al found significant reductions in mean global, GM, and WM cerebrovascular reactivity in chronic TBI individuals by BOLD analysis . However, no significant group difference for CBF was found by ASL analysis.…”
Section: Resultsmentioning
confidence: 97%
“…The age range of all studies was from school level to retirement age (13.5–74 years). Of all included in vivo studies, 22 used an age‐matched control group . All articles were published between 1994 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations